AFFINITY STRATEGY AND AUTHENTIC READING MATERIALS: AN EFFORT TO IMPROVE READING COMPREHENSION - Anak Agung Putri Maharani; Anak Agung Putu Arsana; Ni Luh Putu Dian Sawitri (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2015)
ABSTRACT This research is a classroom action research which aimed at 1) investigating the improvement of the students’ reading comprehension after being treated by Affinity strategy and authentic reading materials and 2) investigating the students’ response about the implementation of Affinity strategy and authentic reading materials towards reading comprehension. For the accomplishment of the research, 41 X IS 2 freshmen of SMA N 7 Denpasar were involved within this research. In garnering the data, reading comprehension test, observation sheet, interview guide, and questionnaire were used as the research instruments. Afterwards, the gained data was analyzed by means of qualitatively and quantitatively descriptive analysis. The first finding of the research is Affinity strategy and authentic reading materials were able to enhance the students’ reading comprehension. It was proven by the mean score gained at the cycle I was 69.65 which was lower than the mean score in cycle II that was 78.75. Both of the mean scores were higher than the mean score of the pre-test which was 63.17. The second finding of the research is that there was a positive response from the students towards the implementation of Affinity strategy and authentic reading materials. This finding was supported by the result of the interview and the questionnaire. The students felt at ease to undergo learning and teaching process within the implementation of Affinity strategy. Affinity strategy assisted the students to construct their knowledge about the passages through connecting their prior knowledge and peers. Moreover, the authentic reading materials provided the students with a real language classroom. Key Words: Authentic reading materials, Affinity strategy, reading comprehension